Climatology of global lightning classified by stroke energy using WWLLN data. (16th February 2015) - Iwasaki, Hiroyuki
ABSTRACT: Climatological features of lightning, based on stroke energy, were studied by considering the hourly detection efficiency of the World Wide Lightning Location Network (WWLLN) data set from April 2009 to April 2014. Five regions were found in which the ratio of strong lightning (>90th percentile of stroke energy) to overall lightning exceeded 30% (high S‐ratio regions), and one region was determined in which the ratio of weak lightning (<10th percentile) to overall lightning exceeded 30% (high W‐ratio region). One region of high S‐ratio was the Tibetan Plateau. Lightning activity and the S‐ratio in this region increased during summer afternoons as rainfall increased; however, the large S‐ratio was observed in the grid where lightning activity was very weak. The four other areas of high S‐ratio were located over the ocean in the sub‐polar climatic zones of the Northern and Southern Hemispheres. In cold seasons of the two hemispheres, when rainfall amount increased, both the lightning activity and the S‐ratio increased, displaying nocturnal maxima; however, the amount of rainfall did not exhibit diurnal variation. Here, a large S‐ratio was also observed in the grid where lightning activity was very weak. Weak lightning activity dominated in the East Pacific. The activity of weak lightning and the W‐ratio showed a tendency to increase during daytime in the cold season. The seasonal variation of the W‐ratio was almost in accordance with rainfall amount; however, diurnal variation of the W‐ratio was not. A large value of the W‐ratio was also observed in the grid where the lightning activity was very weak.